Analysis of the Principles of the Sunt Servanda Pacta in International Criminal Law Enforcement: Implementation and Challenges - Reza Bagoes Widiyantoro; Joko Setiyono (International Journal Labs, 2025)
An essential principle of international law, Pacta Sunt Servanda asserts that all treaties are to be faithfully upheld by all governments. This research addresses the critical problem of how this fundamental principle can be effectively implemented in international criminal law enforcement, particularly given the persistent challenges of state compliance, jurisdictional limitations, and barriers to international cooperation. The research objectives are twofold: (1) to analyze the fundamental position of Pacta Sunt Servanda principles within the framework of international agreements, and (2) to examine the relationship between Pacta Sunt Servanda principles and the application of international criminal law. This study employs a qualitative normative juridical approach with comprehensive document analysis, examining landmark treaties including the 1948 Genocide Convention, the 1949 Geneva Conventions, and the 1998 Rome Statute. The results demonstrate that while Pacta Sunt Servanda serves as the cornerstone of international legal stability, its implementation faces significant obstacles, including state non-compliance, jurisdictional disputes, and political interference. The analysis reveals that successful enforcement requires robust institutional frameworks, as evidenced by cases from the International Criminal Court (ICC) and the International Criminal Tribunal for the Former Yugoslavia (ICTY). The principle's effectiveness varies considerably across different international criminal law contexts, with compliance rates influenced by political, economic, and sovereignty considerations. The implications of this research emphasize that addressing implementation challenges requires enhanced multilateral commitment and strengthened international cooperation mechanisms. The study concludes that while Pacta Sunt Servanda remains fundamental to international justice, ensuring justice for victims of international crimes demands systematic reforms in state compliance monitoring.